2016
DOI: 10.18483/ijsci.904
|View full text |Cite
|
Sign up to set email alerts
|

Economic Contribution of Non-timber Forest Products (NTFPs) to Rural Livelihoods in the Tharawady District of Myanmar

Abstract: Non-timber forest products (NTFPs) income plays an important role in the household economy in the rural forest dwelling communities. This study use the data from 60 sample households of the three villages in Tharwady District of Myanmar to analysis the significant of NTFPs income in the rural household economy. Data collection was carried out through face to face household interview, focus group discussion, and government official interview. This study found that NTFPs income contributes 44.37%, and farm incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Nonetheless, the subsequent occupation and gross annual income of the wicker handicraft entrepreneurs have direct influences on economic development through wicker handicraft, the households with higher subsequent occupation and gross annual income can organize large scale manufacture of wicker handicrafts while the families having lower subsequent occupation and gross annual income can hardly support small scale manufacture of wicker handicrafts only. The results were in consistent with other studies [27][28][29][30][31][32][33] from elsewhere which established that the socioeconomic factors statistically and significantly influenced the household forestbased industrial income dependence.…”
Section: Determinants Of Economic Contribution Of Wickersupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, the subsequent occupation and gross annual income of the wicker handicraft entrepreneurs have direct influences on economic development through wicker handicraft, the households with higher subsequent occupation and gross annual income can organize large scale manufacture of wicker handicrafts while the families having lower subsequent occupation and gross annual income can hardly support small scale manufacture of wicker handicrafts only. The results were in consistent with other studies [27][28][29][30][31][32][33] from elsewhere which established that the socioeconomic factors statistically and significantly influenced the household forestbased industrial income dependence.…”
Section: Determinants Of Economic Contribution Of Wickersupporting
confidence: 92%
“…Nonetheless, the nditions of the wicker handicraft entrepreneurs is far away from the desired level, there is still much scope to improve their quality of life through intervention of specific livelihood diversification strategies. studies [27][28][29][30][31][32][33] across the world have shown the low socioeconomic conditions in the communities heavily reliant on the forest-based industries their livelihood security.…”
Section: Economic Characteristics Of Wicker Handicraft Entrepreneurs mentioning
confidence: 99%
“…Altogether 37.69% of the respondents were illiterate and 10.77 % respondents only had the access to the "upper level" schools and colleges. In addition, according to the age categorized by Mehta and Heinen (2001), younger (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), middle-aged (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), and older ( ≤ 56): 27.69, 44.62 and 27.69 % of the respondents were younger, middle-aged and older respectively. The main wildlife raiding the agriculture crop were one-horned rhinoceros, forest cow and wild boar.…”
Section: Demographic and Socioeconomic Characteristics Of Householdsmentioning
confidence: 99%
“…Forest resources play an important role in the livelihoods of local communities for various products. Forest function as the main source of primary and secondary income for rural household (Moe et al 2016;Langan et al, 2016;Hlaing et al, 2017;Toe et al 2017). Local communities do business in the forest with a pattern that has become a culture of society with an orientation of economic and social needs, while environmental aspects are often an obstacle due to the limited ability of local communities.…”
Section: Introductionmentioning
confidence: 99%
“…Local communities do business in the forest with a pattern that has become a culture of society with an orientation of economic and social needs, while environmental aspects are often an obstacle due to the limited ability of local communities. Furthermore, Moe et al (2016) stated that community forestry (CF) programs should be encouraged to reduce dependence on natural forest. CF programs must be driven by participation of low and middle income household.…”
Section: Introductionmentioning
confidence: 99%